Liquiritin, as a Natural Inhibitor of AKR1C1, Could Interfere With the Progesterone Metabolism - Zeng, Chenming; Zhu, Difeng; You, Jun; Dong, Xiaowu; Yang, Bo; Zhu, Hong; He, Qiaojun (Frontiers in Physiology, 2019)
Low progesterone level is always linked with pre-term birth. Therefore, maintaining of progesterone level is vital during pregnancy. Aldo-keto reductase family 1 member C1 (AKR1C1) catalyzes the reduction of progesterone to its inactive form of 20-alpha-hydroxy-progesterone and thus limits the biological effect of progesterone. In our effort to identify the natural compound that would specifically inhibit AKR1C1, liquiritin was found to be a selective and potent inhibitor of AKR1C1. Kinetic analyses in the S-(+)-1,2,3,4-tetrahydro-1-naphthol (s-tetralol) catalyzed by AKR1C1 in the presence of the inhibitors suggest that liquiritin is a competitive inhibitor by targeting the residues Ala-27, Val-29, Ala-25 and Asn-56 of AKR1C1. In HEC-1-B cells, treatment with liquiritin results in 85.00% of reduction in progesterone metabolism, which is mediated by AKR1C1 enzymatic activity. Overall, our study not only identify liquiritin as an inhibitor against AKR1C1, but also reveal that liquiritin may be served as a potential intervention strategy for preventing pre-term birth caused by low progesterone level.